2018
DOI: 10.1038/s41467-018-03886-6
|View full text |Cite|
|
Sign up to set email alerts
|

The IL-33-PIN1-IRAK-M axis is critical for type 2 immunity in IL-33-induced allergic airway inflammation

Abstract: Interleukin 33 (IL-33) is among the earliest-released cytokines in response to allergens that orchestrate type 2 immunity. The prolyl cis-trans isomerase PIN1 is known to induce cytokines for eosinophil survival and activation by stabilizing cytokines mRNAs, but the function of PIN1 in upstream signaling pathways in asthma is unknown. Here we show that interleukin receptor associated kinase M (IRAK-M) is a PIN1 target critical for IL-33 signaling in allergic asthma. NMR analysis and docking simulations suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 73 publications
(84 reference statements)
3
65
0
Order By: Relevance
“…S3), was detectable promptly after compression and was accompanied by a marked induction of epithelial alarmins, including IL-33 and TSLP. While a supportive activity of these factors has been documented for a variety of accessory immune cells 43,44 , IL-33 and TSLP are central for example to the initiation and enhancement of type 2 response typically seen in asthmatic inflammation [45][46][47][48] . Following compression (3 hr), an increased release of these factors from airway epithelial cells could activate type 2 innate lymphoid cells (ILC2) and augment type 2 inflammation in the lung 43,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…S3), was detectable promptly after compression and was accompanied by a marked induction of epithelial alarmins, including IL-33 and TSLP. While a supportive activity of these factors has been documented for a variety of accessory immune cells 43,44 , IL-33 and TSLP are central for example to the initiation and enhancement of type 2 response typically seen in asthmatic inflammation [45][46][47][48] . Following compression (3 hr), an increased release of these factors from airway epithelial cells could activate type 2 innate lymphoid cells (ILC2) and augment type 2 inflammation in the lung 43,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…ATRA binds and induces degradation of Pin1 and its substrate PML‐RARA and thereby exerts anticancer activity against APL in cell and animal models and human patients . This anticancer activity of ATRA has been confirmed and expanded to breast cancer, liver cancer even using a different ATRA controlled release formulation, and acute myeloid leukemia (AML), as well as in lupus and asthma . However, the role of Pin1 in mediating ATRA anticancer activity against gastric cancer is not known.…”
Section: Discussionmentioning
confidence: 99%
“…ATRA‐induced Pin1 ablation also exerts antitumor activity against breast cancer by blocking multiple oncogenic pathways . The ability of ATRA to inhibit Pin1 function has been independently confirmed in breast cancer and also expanded to liver cancer, even using a different ATRA controlled release formulation, as well as to lupus and asthma . Although a small study of 182 cases has shown Pin1 overexpression in human gastric cancer, the role of Pin1 in the development and treatment of gastric cancer is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the eventual presence of co-morbidities can induce changes in cancer genetics, molecular, and clinical outcomes, complicating both epidemiologic and mechanistic studies. In fact, several genes and related products involved in highly prevalent illnesses strongly concur to cancer heterogeneity, i.e., hypertension [ 14 , 15 , 16 ], diabetes [ 17 ], allergies [ 18 , 19 , 20 , 21 ] and inflammatory chronic diseases [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%